2014
DOI: 10.1111/ijcs.12112
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation analysis of US older adults living in multifamily housing: reasons for moving

Abstract: This study investigated multifamily housing consumer profiles among the US people age 55 and above based on their reasons for moving into current multifamily housing. A total of 431 samples were collected by an online research survey company using convenience sampling. The three reasons for moving were found from an exploratory factor analysis: the multifamily living reason, the nearby activities reason and the financial reason. A cluster analysis uncovered three groups of multifamily housing consumers: the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A definition of aging-in-place was provided at the beginning of the survey questionnaire. Questions were developed based on Wiseman's (1980) elderly migration process model, Litwak and Longino's (1987) elderly migration framework, and other relevant literature (Kwon & Beamish, 2014;Oswald et al, 2007). Wiseman (1980) proposed a conceptual model of push and pull factors and indigenous and exogenous factors that influence on the decision to remain in a current home or to move based on the aging-related triggering mechanisms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A definition of aging-in-place was provided at the beginning of the survey questionnaire. Questions were developed based on Wiseman's (1980) elderly migration process model, Litwak and Longino's (1987) elderly migration framework, and other relevant literature (Kwon & Beamish, 2014;Oswald et al, 2007). Wiseman (1980) proposed a conceptual model of push and pull factors and indigenous and exogenous factors that influence on the decision to remain in a current home or to move based on the aging-related triggering mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…Litwak and Longino (1987) suggested three groups of seniors who consider relocation based on their health and financial status. Other studies (Kwon & Beamish, 2014;Oswald et al, 2007) emphasized the importance of accessible housing design and local amenities and services for aging-in-place. This current study identified 35 reasons for aging-in-place items related to health condition, financial situation, familial status, and housing condition, and neighborhood.…”
Section: Methodsmentioning
confidence: 99%
“…Multifamily housing tends to be in closer proximity to local serrvices because it is a denser housing type. Such features may be beneficial for senior residents who want to downsize, to avoid performing their own home maintenance, and who want to enjoy amenities at an affordable price (Urban Land Institute, 1991; Haughey, 2003;Kwon & Beamish, 2014). However, there are few studies of senior residents living in multifamily housing in the United States.…”
Section: Background and Purposementioning
confidence: 99%
“…Researchers have argued that multifamily housing could be a viable housing option for older adults, because of the advantages of little to no home maintenance, lower upfront costs, and the variety of amenities and services (Goodman & Scott, 1997;Bookout, 1998;Kwon & Beamish, 2013). In addition, U.S. federal government specifies affordability and accessibility of multifamily housing in law.…”
Section: Us Multifamily Housingmentioning
confidence: 99%